FAKTOR-FAKTOR YANG MEMPERNGARUHI STRUKTUR MODAL DENGAN FAMILY OWNERSHIP SEBAGAI VARIABEL MODERASI - Anastasia, Levika; Rasyid, Ardiansyah (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
The purpose of this study was to examine the effect of profitability, liquidity, and firm size on capital structure with family ownership as a moderating variable. The sampling technique in this study used the non-probability sampling method and the purposive sampling method as the sample selection method. This study uses 300 samples from 75 manufacturing companies listed on the Indonesia Stock Exchange for the period 2017-2020. The data in this study were obtained from financial statements and processed using Microsoft Excel and Spss 16 programs with multiple linier regression analysis. The results of this study indicrate that profitability has a significant negative effect on capital structure, while firm size has a significant positive effect on capital structure. In additional, family ownership as a moderating variabel strengthens the relationship between profitability and capital structure. For the liquidity variable, and the firm size of the company family ownership does not moderate the relationship between each variabel on tehe capital structure.